Excitation by shot circuited coaxial transducer of magnetostatic modes in rectangular yttrium iron garnet film - Babichev, Rudolf Karpovich; Babicheva, Galina V (Известия высших учебных заведений: Прикладная нелинейная динамика, 2022)
The purpose of this work is the study of design of new short-circuited coaxial transducer with thin linear jumper, that circuites on both sides of the grounded coaxial cylinder, located above the rectangular iron-yttrium garnet (YIG) film, in homogeneous constant magnetic field with rectangular film along its length or width. The thin linear jumper is directed parallel to the width of the YIG film. Methods. In the CST Microwave Studio environment, an electrodynamic analysis of the model was carried out using the finite element method. To study the efficiency of modes excitation in a ferrite film at different distances between the coaxial transducer and the surface of the YIG film, the frequency dependencies of the inverse losses S11 of the model were calculated. Results. 1. The identification of modes in a homogeneous static magnetic field H, directed parallel to the plane of a rectangular YIG film along its width (y-axis) was carried out. 2. The identification of modes in a homogeneous static magnetic field H directed parallel to the plane of the rectangular YIG film along its length (z-axis) was carried out. 3. A comparison of modes spectra was made at H, directed parallel to the plane of the YIG film along its width (y axis) and length (z axis). Conclusion. In this paper short-circuited transducer with a thin linear jumper, circuited on both sides of the grounded coaxial cylinder, is investigated. By the electrodynamic method distributions of high-frequency magnetic field of the excited magnetostatic modes were calculated and their identification was carried out for two directions of homogeneous static magnetic field: along width and along length of rectangular YIG film. The dependence of number of excited modes on the distance between a short-circuited transducer and rectangular YIG was also studied. A comparison of modes spectra is carried out at H, directed parallel to the plane of the YIG film along its width and length. With this rotation of H vector, the band of effectively excitable modes shifts from 4.6...4.9 GHz to 4.5...4.75 GHz. However, the excitation of these modes in the case of the vector H, directed along the width of YIG film (z-axis), is much more effective in the band 4.65...4.9 GHz than in the case when this vector is directed along the length of YIG film (z-axis). At the same time, excitation of these modes in the case of the vector H, directed along the length of YIG film (z axis) is much more effective in the band 4.4...4.6 GHz.